Compendium of New Techniques in Harmonic Analysis - Tahar Lamchich, Moulay (IntechOpen, 2018)
Harmonic analysis is a diverse field including such branches as signal processing, medical imaging, power electrical systems, wireless telecommunications, etc. This book is primarily written with the objective of providing recent developments and new techniques in harmonic analysis. In the recent years, a number of methods of quality control of signals under different perturbations, and especially the harmonics, have emerged. Some of these techniques are described in this book. This book is the result of contributions from many researchers and is a collection of eight research works, which are focused around the harmonic analysis theme but with different applications. The topics mainly concern the areas of medical imaging, biopotential systems, renewable energy conversion systems, wireless telecommunications, power converters, as well as the different techniques for estimating, analyzing, reducing, and eliminating harmonics.